Mimicking women’s endocrine milieu in mice for women’s health-related studies - Céline Constantin; Daria Matvienko; Csaba László; Valentina Scabia; Laura Battista; Pierre-Alain Binz; Stephen J. Bruce; Cathrin Brisken (npj Women's Health)
Abstract To improve preclinical studies and their translation, patient-derived xenografts (PDXs) are increasingly used. They have human-specific tumor characteristics and reflect intra and inter-tumor heterogeneity. However, the endocrine milieu differs between humans and host mice. In light of sex-specific cancer biology and a rise in endocrine-related cancers there is an urgent need to correctly reflect the hormonal milieu in PDX models. We show that female mice of NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) strain widely used for PDXs has 17-β-estradiol (E2) and testosterone (T) levels comparable to C57Bl6 females but higher progesterone (P4) levels. E2 levels are comparable, T levels are lower and P4 levels higher than those observed in postmenopausal women. Ovariectomy increases T to levels observed in postmenopausal women. Subcutaneous E2 and combined E2/P4 silicon pellets provide NSG females with premenopausal ovarian hormone levels. These procedures humanize the endocrine environment of experimental animals, improving PDX relevance in women’s health-related research.